Software implementation of the NSA’s ARADI block cipher on Arm Cortex–M4 - Rabelo, José Eduardo Santos; López, Julio (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2026: Anais do XXVI Simpósio Brasileiro de CibersegurançaDO - 10.5753/sbseg.2026.29334, 2026)
ARADI is a block cipher proposed by the NSA for inline memory encryption and paired with LLAMA, an authenticated-encryption mode for low-latency memory protection. This work evaluates the software viability of the NSA’s ARADI block cipher on a 32-bit Arm Cortex–M4 microcontroller. We derive an optimized linear map and a shuffle-based two-block formulation that leverages packed halfword parallelism. Our optimized implementation achieves a 2.36× performance improvement over the two-block NSA baseline. Finally, we provide comparative benchmarks against ChaCha–Poly1305 and AES-256.